ANALISIS KELAYAKAN BUKU TEKS KIMIA SMA/MA KURIKULUM 2013 PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Ulfah, Masita (Journal of Technique Research (JTR), 2019)
The research aims to analyzing the feasibility textbook of chemistry in curriculum 2013. The research used descriptive methods with qualitative approach. The techniques to collect the data were library study with reading and analyze the whole data. The data resource was text book of Chemistry Based on Student Experiments for Class X SMA/MA Specialization in Mathematics and Natural Sciences Specialization Group on Electrolyte and Non Electrolyte Solution Materials published by the Ministry of Education and Culture.The results of the researchers show that chemistry book class X in terms of Conformity of material description with KI and KD, breadth and depth of material, material accuracy, and learning support material is said to be worthy. The material presented supports the achievement of KI and KD. The material presented in this chapter is very complete. The concepts and definitions of material in textbooks are also presented accurately to avoid misconceptions and in accordance with technological developments.